STUDI KEBUTUHAN MASYARAKAT TERHADAP BUS SEKOLAH DI KOTA SORONG - Sianturi, Lidwina Sri Ayu DR; Sabarofek, Albert Eliezar; Leo, Edison; Angkat, Hokbyan R.S (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2025)
The free school bus program is a transportation solution that enhances students' accessibility to education, reduces traffic congestion, and improves travel safety. This study aims to analyze the technical feasibility and develop an operational plan for free school buses in Sorong City. The research employs a quantitative descriptive analysis approach through surveys using questionnaires distributed to students and parents. The number of respondents in this study was 159 people who lived in several sub-districts in Sorong City. The collected technical data includes road conditions, route characteristics, passenger capacity, as well as safety and operational efficiency aspects. Operational planning considers factors such as the required number of buses, operational schedules, travel distances, and strategies for service optimization. The results of this study show that the majority of respondents do not have free school buses in their area and feel that this program is very important to support the learning process of students. Quantitative descriptive analysis shows that respondents' agreement with the program is quite diverse regarding routes, fares and service models. Abstrak Program bus sekolah gratis merupakan salah satu solusi transportasi yang dapat meningkatkan aksesibilitas pelajar terhadap pendidikan, mengurangi kemacetan, serta meningkatkan keselamatan dalam perjalanan ke sekolah. Penelitian ini bertujuan untuk menganalisis kelayakan teknis dan menyusun perencanaan operasional bus sekolah gratis di Kota Sorong. Metode penelitian yang digunakan adalah analisis deskriptif kuantitatif dengan pendekatan survei melalui kuisioner kepada pelajar dan orang tua. Jumlah responden dalam penelitian ini adalah sebanyak 159 orang yang tinggal di beberapa kelurahan di Kota Sorong. Data teknis yang dikumpulkan meliputi kondisi jalan, karakteristik rute, kapasitas penumpang, serta aspek keselamatan dan efisiensi operasional. Hasil Penelitian ini menunjukan bahwa mayoritas responden belum memiliki bus sekolah gratis di daerah nya, dan merasa program ini sanggat penting untuk menunjang proses belajar para siswa. Analisis deskriptif kuantitatif menunjukan bahwa persetujuan responden tentang program ini cukup beragam mengenai rute, tarif dan model layanan.